Fission Yields Evaluation for Xe Isotopes from nF+235U - CAO Chaowei1, LI Chang1, 2, SHU Nengchuan1, , LIU Ling2, , SU Yang1, CHEN Yongjing1, LIU Lile1 (Yuanzineng kexue jishu, 2024)
Fission yield is one of important basic nuclear data in nuclear engineering applications and nuclear physics research, especially for the fission gas products which have non-negligible impact on the design and operation of nuclear devices. Therefore, evaluating and providing a set of new yields for the gas products with more liability is of great significance to the nuclear application and basic research. The traditional fission yield evaluation method usually evaluate the specific fission yield (such as independent fission yield) of a certain nucleus separately, did not consider the physical relations between the products on the same decay chain, even the other chain which may have contribution through beta-n decay. And this may result to the inconsistency among yields of these products. For an example, 131Xe is contributed from the nF+235U fission and precursor’s (131I and 131Xem) decay, so its cumulative yield should be the summation of the independent yields of and 131Xe, 131Xem and the cumulative yield of 131I. It can not satisfy the needs from the engineering applications. In order to solve the inconsistency problem, a unified evaluation method was developed based upon the Zp model, which can describe the independent and cumulative fission yields simultaneously for the products on the same mass chain A, wherein the decay branches are the connections between the two types of the yields. There are 4 parameters in the model, which are obtained by fitting to experimental cumulative and independent fission fields, and consequently the fission yield could be reproduced. In this work, the model was applied to evaluation the yields of Xe of 235U fission induced by fission neutron, where the experimental data were collected from EXFOR library. Comparisons were performed between the present work and the data from ENDF/B-Ⅷ.0 and JEEF-3.3. For 131Xe, the present value is little higher than that of ENDF/B-Ⅷ.0 and lower than that of the JEFF-3.3 consider the contribution of the precursor 131I. For 135Xe, the present value is lower than the measured values due to the limit from value of the 135Cs. For 137Xe, the present value is a little higher than the value from JEFF-3.3 also due to the backward limit from the daughter 137Cs yield and agree with the value from ENDF/B-Ⅷ.0. For 139Xe, the present data is closer to the measured datum. To sum up, the Xe yields of nF+235U fission are re-evaluated with unified method, and consistent with the yields along the mass chain. The results show the present evaluated data are more reasonable since all the data are used on the decay chain, not only the measured data for Xe its own self. This method could be applied to evaluate other yields.